Política de venta en el Comercial MARTH de la ciudad de Milagro Provincia del Guayas - Zurita García, Lastenia Edith (2021)
In this project, a complete study of the elements that will allow the improvement of Comercial Marth is carried out, it starts from detecting the causes and effects to determine the relevance of the project and technically support the elements necessary for its execution. Once the case study has been carried out, it will consist of a detailed organizational structure of the business that includes Financial, Administrative, Tax, Audit and Control Management, in relation to the subline of investigation of the Public and Private Companies and Institutions model. Another relevant aspect is the financial analysis that reveals the stability of sales or their low income, therefore the information obtained is strictly attached to the needs of the company so that decisions are made according to the objectives set. . An excellent administration will help to achieve the goals, the administration has to make sure that everything works well and the complete satisfaction of the clients is reflected in the performance of the employees both in the administrative and operational areas and the company will be able to see the results in the Income that would not be reflected if a poor quality service is provided, for the administration to function properly it has to apply its planning, organizing and controlling skills effectively.